2013
DOI: 10.1021/jp404518r
|View full text |Cite
|
Sign up to set email alerts
|

Free Energies of Binding from Large-Scale First-Principles Quantum Mechanical Calculations: Application to Ligand Hydration Energies

Abstract: Schemes of increasing sophistication for obtaining free energies of binding have been developed over the years, where configurational sampling is used to include the all-important entropic contributions to the free energies. However, the quality of the results will also depend on the accuracy with which the intermolecular interactions are computed at each molecular configuration. In this context, the energy change associated with the rearrangement of electrons (electronic polarization and charge transfer) upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 55 publications
0
73
0
Order By: Relevance
“…A very wide range of such approaches has been developed [5], with widely-used implementations including the Polarisable Continuum Model (PCM) [128], the COSMO model [129], the SMD model [130], and the unified electrostatic and cavitation model of Scherlis et al [131]. An adaptation of the latter by Dziedzic et al [132] has recently been demonstrated for application to entire proteins [133,134].…”
Section: Electrostatics and Implicit Solvationmentioning
confidence: 99%
See 1 more Smart Citation
“…A very wide range of such approaches has been developed [5], with widely-used implementations including the Polarisable Continuum Model (PCM) [128], the COSMO model [129], the SMD model [130], and the unified electrostatic and cavitation model of Scherlis et al [131]. An adaptation of the latter by Dziedzic et al [132] has recently been demonstrated for application to entire proteins [133,134].…”
Section: Electrostatics and Implicit Solvationmentioning
confidence: 99%
“…First, a hybrid Monte Carlo simulation generates a statistically-rigorous QM/MM ensemble of structures from the underlying MM ensemble [291]. Once this ensemble has been generated, a single-step free energy correction may be computed using the approach of Fox et al to transform the QM/MM hydration free energies to the full QM result [134]. The idea behind the stepping stone approach is that, in the QM/MM ensemble, the polarisation of the ligand by the surrounding solvent is accounted for and, hence, it should provide a much closer representation of the target QM ensemble.…”
Section: Towards Rigorous Quantum Free Energies Of Bindingmentioning
confidence: 99%
“…The simplest method to obtain free energy differences via Hamiltonian reweighting involves reweighting from one sampled to one unsampled state, generally referred to as exponential reweighting or the Zwanzig equation [191,238,240,[242][243][244][247][248][249][250]252], which is simply eq 6.1. This method produces asymptotically unbiased free energy differences in the limit of large sampling.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Warshel et al [238] introduced a method based on the pioneering work of Kirkwood [239] and Zwanzig [191] to calculate free energies in complex Hamiltonians indirectly by simulating in a cheap potential and calculating ensemble averages in the expensive potential using Boltzmann reweighting, thus avoiding direct simulation in the expensive potential [240][241][242][243][244][245][246][247][248][249][250][251][252][253][254][255][256][257][258]. The formula for estimating the ensemble average in a target state given samples in another state is [191]:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation